Spatial Ecology, Thermal Biology and Prey Behaviour of the Bornean Keeled Pit-viper, Tropidolaemus subannulatus (Reptilia: Squamata: Viperidae) - Veronica, Martin (Malayan Nature Journal, 2022)
The Bornean Keeled Pit-viper, Tropidolaemus subannulatus is a relatively common and widespread species of venomous snake of medical importance in south-east Asia. Nonetheless, knowledge of its biology had remained largely unknown, representing a challenge for both conservation and management on one hand, and public health on the other. This study aims to contribute to the knowledge of a tropical ectothermic vertebrate, leading to an enhanced understanding on its spatial biology, foraging behaviour and thermoregulation. A total of 21 snakes were encountered at Kubah National Park, Sarawak, East Malaysia (Borneo), during the study period (June 2018 to October 2021). Seven of these were qualified for tracking, based on mass and other telemetric limitations, and five (three females and two males) tracked between October 2019 and January 2020. Each individual was implanted with a temperature-sensitive radio-transmitter to locate individuals, as well as to record microhabitat use and internal body temperature. Microhabitat assessments were conducted during these field study. Analysis of feeding behaviour was conducted in a controlled environment in the lab. An ethogram was prepared based on video footage captured with a HDD camera. All individuals of T. subannulatus tracked revealed a relatively small home range (mean 100% MCP 303.51 m2), as well as limited movement (mean horizontal = 20.89 m, mean vertical = 13.03 m). Horizontal displacements were limited, while vertical movements were relatively more substantial, albeit challenging, with visuals of snakes bearing transmitters difficult to obtain at times due to dense vegetation, especially when snakes used high canopy microhabitats of tall trees, including Xanthophyllum griffithii and those of the genus Shorea. Apart from occasional changes in posture, T. subannulatus can remain motionless for days or weeks. There are no significant differences in movement and home range between the sexes of Tropidolaemus subannulatus. This study found that the pit-vipers were found to utilize tree branches, saplings, twigs and ferns, while over 80% of the time were found on tree branch. Males were found to only utilized tree branches and saplings, probably due to their pronounced sexual dimorphism. Thermal studies showed a wide temperature variation, between 22.97°C and 30.56°C. Core body temperature and body surface temperature displayed significant differences (P < 0.001), suggestive of a thermoconformer rather than a thermoregulator, as may be expected of many ectothermic tropical vertebrates that are nocturnal. Although weakly correlated, there was a significant relationship between ambient temperature with core body temperature (r = 0.209) and surface body temperature (r = 0.298). Substrate temperature have significant relationship with core body temperature (r = 0.671) and surface body temperature (r = 0.993), with stronger correlation compared to ambient temperature. Ex-situ feeding behavioural experiments showed eight common predatory behaviour (head shift, eye fix, approach, strike, wait, upper jaw retraction, gape, tongue flick) that can be classified into three different phases, namely, pre-capture, feeding, and post-feeding phases, during experiments with new-born Rattus norvegicus. Understanding spatial use, thermoregulation, the foraging and prey-handling behaviour are critical. These can provide important insights into evolutionary fitness, as well as the biotic and abiotic factors associated with the focal species. Such studies of tropical snakes of medical importance are vital for development of effective plan of action for conservation as well as public health.